The Effect of Earning Per Share (EPS), Return On Equity (ROE) And Debt to Equity Ratio (DER) To Stock Price (Study On Mining Companies and services Listed In Indonesia Stock Exchange Period 2015-2019 - Firda Febriarianti; Yanna Eka Pratiwi; Siwidyah Desi Lastianti (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2024)
This study aims to determine the effect of earnings per share (EPS), return on equity (ROE) and debt to equity ratio (DER) simultaneously and partially to stock prices in mining companies and services listed on the Indonesia Stock Exchange period 2015-2019. The population in this study is the financial statements of mining companies and services listed on the Indonesia Stock Exchange period 2015-2019 as many as 12 companies. The sampling technique used is purposive sampling method. Based on the research criteria there are 10 companies that meet the criteria of sampling. Data were obtained from financial reports published by Indonesian Capital Market Directory (ICMD) and collected by documentation method.To analyze the data used (1) classical assumption test consisting of normality test, multicollinearity test, autocorrelation test and heteroscedasticity test, (2) multiple linear regression test and (3) hypothesis test consisting of coefficient of determination, simultan significant test (f-test) and partial significant test (t-test). Based on the test results of determination coefficient magnitude Adjusted R Square value of 0,721 or 72,1%. This means that the influence of EPS, ROE and DER variables to the stock price is 72,1% and the remaining 27,9% is influenced by other variables that do not enter into this model/observation. The results showed that simultaneously EPS, ROE, and DER variables significantly influence the stock price. Partial test results show the earning per share (EPS) has a positive and significant effect on stock prices. Variable return on equity (ROE) has a negative and insignificant effect on stock prices. While the variable debt to equity ratio (DER) has a negative and insignificant effect on stock prices.